Free Inquiry Methods: Upaya Meningkatkan Kreativitas dan Minat Belajar Siswa pada Mata Pelajaran Sejarah Indonesia di SMA Negeri 1 Gondang, Bojonegoro - Hilal Nur Fuadi (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2020)
This research aims to improve the creativity and interest of learning students of SMA Negeri 1 Gondang, Bojonegoro, school year 2019/2020. Learning activities using the Free Inquiry method is devoted to the subjects of Indonesian history on the material acculturation of Hindu-Buddhist culture and local culture in Indonesia in grade X students IPS-2. This research uses the method of research actions in two cycles, with qualitative descriptive data analysis. The results showed that the implementation of the free inquiry method can improve the student's creativity and spirit in learning the history and culture of Indonesia in realizing the religious moderation attitude.